2016
DOI: 10.18203/2394-6040.ijcmph20163362
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate breastfeeding practices among lactating mothers: a community based study in rural anganwadi centers in field practice area of government medical college, Jabalpur, Madhya Pradesh, India

Abstract: A study to evaluate breastfeeding practices among lactating mothers: a community based study in rural anganwadi centers in field practice area of government medical college, Jabalpur, Madhya Pradesh, India INTRODUCTIONUnder any circumstances, breast milk is the ideal food for the infant. No other food is required by the baby until 6 months after birth. Feeding the baby exclusively on breast milk, without any other source of nutrition for a period of 6 months is called exclusive breast feeding. 1 A child who i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In this study 93.8% infants burped after feeds. Singh N et al 8 in their study found that 86.67% infants burped after feed which is similar to our study. Whereas study conducted by Benakappa et al 13 found that 58% infants burped after feed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study 93.8% infants burped after feeds. Singh N et al 8 in their study found that 86.67% infants burped after feed which is similar to our study. Whereas study conducted by Benakappa et al 13 found that 58% infants burped after feed.…”
Section: Discussionsupporting
confidence: 92%
“…In this study 56.7% mothers practiced of exclusive breast feeding to their children while studies done by Arage Get al 6 , Mise PJ et al 4 , Kumar L et al 5 found exclusive breast feeding rate of 70.8%, 63.4% and 86.8% respectively.In this study working status of mother did not show statistically significant association with exclusive breast feeding. Similar finding is reported in study conducted by Singh N et al 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Further, three mothers (15%) experienced an inverted nipple, which is described as a reason by mothers for discontinuing breastfeeding. However, an inverted nipple can be treated with proper consultation with doctors (Singh et al, 2016).Out of 20 mothers, 11 (55%) of them experienced intermittent headache; 13 (65%) of them felt fatigued and 11 (55%) mothers experienced disturbed sleep due to frequent breastfeeding the baby during night time and had redness of the eyes. (Waldenstrom, 2004) stated that in general, lactating mothers breastfeed their children often every two hours in the daytime, which results in back pain and tiredness.…”
Section: Physical Dimensionsmentioning
confidence: 99%